Armenian Immigration to Syria in the Ottoman Reign - ALAWI SHAMKI JABER, BAYDAA (Al-Adab Journal, 2019)
The study showed clearly the historical roots of the Armenian migrations to Syria, and put the first building blocks of the beginnings of these migrations, which was built on the basis of which after a while commercial and social relations between the Arabs and Armenians. As shown on the Armenian issue and its causes, and it seems that this picture was accurately reflected during the fears of the Ottomans of the Russians, They were complaining about the loyalty of the Armenians to them, and think that the existence of contacts between the Russians and the Armenians to hit the rear of the Turkish army and disrupt its operations, and they are working as spies for the Russians.The study also confirmed the most important Armenian massacres and the displacement and distribution of Armenians in Syria, the late Ottoman period.